Projective limits of state spaces I. Classical formalism - Lanery, Suzanne; Thiemann, Thomas (Journal of Geometry and Physics, 2017)
The present first paper aims at clarifying the classical structures that underlies this formalism, namely projective limits of symplectic manifolds [27, subsection 2.1]. In particular, this allows us to discuss accurately the issues hindering an easy implementation of the dynamics in this context, and to formulate a strategy for overcoming them [27, subsection 4.1]. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Field theory; Projective limits; Symplectic geometry; Algebras of observables; Constrained Hamiltonian systems